Between two worlds: representations of the rural and the urban in two Portuguese municipalities - Mendes, M.; Carmo, R. M. (International Journal of Applied Sociology, 2013)
In a context of contemporaneousness in which there is little mention of the articulation between urban spaces and those with predominantly “rural” characteristics, we seek to make a contribution towards the “social construction of the rural space” and towards an understanding of the relation spheres and articulation between these spaces and the dynamics of urbanisation. This analysis was conducted within the context of a larger study that used several tools for gathering information (analysis of secondary data, questionnaires and interviews) in seeking to understand the principle recent transformations in the more peripheral and rural areas of the Algarve region. The Algarve is better known, both nationally and internationally, as an attractive tourist destination for those seeking sun and accessible beaches; however, it is also a very diverse region (with mountainous and rural landscapes), and one, moreover, little studied by the social sciences. Here we discuss and problematize social representations of the local space by the residents of two municipalities: São Brás de Alportel and Alcoutim. Based on the results of a study concluded in 2010, we discuss the responses to a survey of 678 residents in both municipalities (the questionnaire was given to a representative sample of residents according to gender and age [2001 Census]), in order to understand their views on the development of their municipality, about the area’s strong and weak points and about the main changes taking place in respect of the (re)composition of the local population. These two municipalities, which are very different despite their geographical proximity, were selected in order to allow an analysis of long-term structural changes; however, here we are particularly interested in discussing some of the exploratory analysis indicators associated with the respondents’ subjective perceptions. The representations by residents of both municipalities are various and contrasting, with asymmetries and diversities between them. This analysis leads us to a conclusion in respect of the limits on the use of conceptions that are naturalist, a priori and which are based on the reification of the spatial characteristics and social practices of social protagonists within rural spaces. It is necessary to devise alternative conceptual tools, ones that take into consideration the relational spaces promoting the dynamics of inter-relationship, diversity and of hybridism that must be incorporated into socio-territorial and multi-scale projects and policies (local base, connected to the national and the international).